2000
DOI: 10.1002/1097-4628(20001114)78:7<1402::aid-app110>3.3.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Effect of crosslinking on mechanical and viscoelastic properties of semiinterpenetrating polymer networks composed of poly(vinyl chloride) and isocyanate crosslinked networks

Abstract: Semiinterpenetrating polymer networks (SIPNs) of PVC/isocyanate/polytriol were prepared by premixing small (150 m dia.) porous (30% voids) unplasticized PVC particles, 10% by weight of isocyanate, and a triol at different OH/NCO mol ratios. Three types of isocyanates (methylene bis-phenyl diisocyanate (MDI), oligomeric MDI isocyanates (PAPI), and toluene diisocyanate (TDI) prepolymer/polytriol) were used. Two-roll milling was followed by hot-press curing. The tensile, flexural, and impact strengths increased w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Hence, thermal stability of the composite scaffold was found to be increased after crosslinking. It was also revealed that the highest degradation temperature increased in the sequence of GP, CGP, GPCT, CGPCT which was the same as that of their crystallinity, implying thermal stability of the films was improved by their crystalline domains and hydrogen bonding interactions 34…”
Section: Resultsmentioning
confidence: 84%
“…Hence, thermal stability of the composite scaffold was found to be increased after crosslinking. It was also revealed that the highest degradation temperature increased in the sequence of GP, CGP, GPCT, CGPCT which was the same as that of their crystallinity, implying thermal stability of the films was improved by their crystalline domains and hydrogen bonding interactions 34…”
Section: Resultsmentioning
confidence: 84%
“…The curing rate of monomers is critical as it can prevent and/or limit the phase separation of the system [16]. By controlling the kinetics of both polymerization reaction and microphase separation, it is possible to prepare IPNs with dispersed phase domains ranging from a few tens of nanometers to a few micrometers [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The weight loss at 400-600 ºC was believed to be caused by oxidation and degradation 39 . The pure WPU film exhibited one weight loss step in the course of thermal degradation and the initial thermal decomposition occurred on 357 ºC and then, decomposed to give greatest weight loss in 380 ºC, which may be caused mainly by the breaking of urethane bonds 40 . The thermo-gravimetric trace of CMGG revealed that decomposition of CMGG was a single step degradation process, which decomposition started at 247 ºC and proceeded at a faster rate up to 290 ºC.…”
Section: Thermal Properties Of the Blend Filmsmentioning
confidence: 99%